Composition controlled nickel cobalt sulfide core–shell structures as high capacity and good rate-capability electrodes for hybrid supercapacitors. Issue 55 (23rd May 2016) - Zhang, Lei; Zhang, Haitao; Jin, Long; Zhang, Binbin; Liu, Fangyan; Su, Hai; Chun, Fengjun; Li, Qinghan; Peng, Jinfang; Yang, Weiqing
Abstract : Tuning element content is an effective approach for achieving excellent rate-capability and cycling stability in polynary metal sulfides for hybrid supercapacitors. Abstract : Herein, we report a type of core–shell structured Ni x Co3− x S4 ( x = 1, 1.5 and 2) through tuning the ratios of Ni to Co by a simple two-step hydrothermal method. Scanning electron microscopy and transmission electron microscopy images of all the Ni–Co sulfides show high porosity and uniform spherical morphology. Moreover, this study demonstrates that controlling the appropriate ratio of Ni to Co in the core–shell structure is crucial for improving the electrochemical performance in a hybrid supercapacitor. Among them, NiCo2 S4 with core–shell structure possesses the highest capacity of 155 mA h g −1, whereas as Ni1.5 Co1.5 S4 shows the excellent rate-capability of up to 80% from 1 to 20 A g −1 and cycling stability, which retains 74% after 2000 cycles. Therefore, tuning the metal element contents provides a feasible approach to achieving the desired high-rate performance and cycling stability of electrode materials in polynary metal sulfides for hybrid supercapacitors.